Self-assessment of attitudes towards conditions to provide safe abortion among new medical graduates in Thailand, 2018: an application of cross-sectional survey with factor analysis - Nithiwat Saengruang; Nisachol Cetthakrikul; Anond Kulthanmanusorn; Somtanuek Chotchoungchatchai; Nareerut Pudpong; Rapeepong Suphanchaimat (BMC, 2021)
Abstract Background Unsafe abortion is one of the major public health problems in Thailand. Although the penal code of Thailand and the Thai Medical Council permit doctors to perform safe abortion in certain conditions, little is known about the attitudes that new medical doctors have towards abortion. The objectives of this article are to explore the attitudes towards abortion in certain conditions among new medical graduates and to identify factors related to those attitudes. Methods A cross-sectional survey was conducted in 2018 among 2017 medical graduates who attended the annual workplace selection forum. The participants came from the two main tracks of admission to Thai medical schools: normal track and special track physicians, namely, the Collaborative Project to Increase Production of Rural Doctors (CPIRD). Of these 2017 graduates, 926 returned the questionnaire with complete information. Descriptive analysis, factor analysis, and multi-variable regression analysis were performed. Results We found that most physicians agreed to perform abortions in the context of life-threatening conditions for mothers and children, but not under conditions directly related to physical health (such as pregnancy with socioeconomic problems or pregnancy in adolescents). CPIRD doctors were less amenable than normal track doctors in providing abortions if the reason for the termination of pregnancy was related to socioeconomic problems. Conclusion The study suggests that a proactive campaign for new medical graduates to raise awareness and mutual understanding of abortion services should be exercised. The CPIRD curricula relating to safe abortion should enhance the capacity of medical graduates to deal with pregnant women who face not only a physical health-related problem, but also socioeconomic difficulties and well-being as a whole.